Aplicação de análise ergonômica do trabalho auxiliada por pontos de verificação ergonômica e aplicação de conceitos de aprendizagem expansiva - Almeida, Flavio Coutinho (2021)
Among the most widespread forms of practical application of ergonomic concepts, the activity centered ergonomic analysis stands out. This study aims to apply the Ergonomic Checkpoints Points (ECP) tool in activity centered ergonomic analysis, via Case Study method, to investigate possibilities of expanding the limits of collaborative solving of problems and the proposing of collective solutions, by using Expansive Learning concepts, from Cultural Historical Action Theory. This approach was applied in an environment characterized by access restrictions and lack of qualified personnel for doing more complex analyses, and in which the initial demand was focused on the design of artifacts in a small company of veterinary services. As results, we could point out the novelty represented by the joint application, in a case study, of concepts of Expansive Learning in situated ergonomic analysis, guided by ECP, resulting in aspects of learning and collective knowledge construction, bringing better situational awareness about ergonomic problems that affect the company, its operational context and the expansion of the consensual figuring of problems by company’s professionals, as immaterial aspects. As material results, we could cite data for establishing specifications, drawings and prototypes, instrumental for the development of solutions, through artifacts.